2008
DOI: 10.1016/j.brainres.2008.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the ontogeny of the vesicular glutamate transporter 3 (VGLUT3) with VGLUT1 and VGLUT2 in the rat retina

Abstract: Glutamate is the major excitatory neurotransmitter in the retina, and most glutamatergic neurons express one of the three known vesicular glutamate transporters (VGLUT1, 2, or 3). However, the expression profiles of these transporters vary greatly in the retina. VGLUT1 is expressed by photoreceptor and bipolar cell terminals, and VGLUT2 appears to be predominately expressed by ganglion cells, and perhaps Müller cells, cone photoreceptor terminals, and horizontal cells in some species. The discovery of a third … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 52 publications
7
21
0
Order By: Relevance
“…The SD rat retinas showed that VGluT1 immunoreactivity followed previously reported patterns (Gong et al, 2006;Stella et al, 2008) (Fig. 4A).…”
Section: Kcnq5/vglut1supporting
confidence: 69%
See 2 more Smart Citations
“…The SD rat retinas showed that VGluT1 immunoreactivity followed previously reported patterns (Gong et al, 2006;Stella et al, 2008) (Fig. 4A).…”
Section: Kcnq5/vglut1supporting
confidence: 69%
“…VGluT1 is a marker of all the photoreceptor terminals in the OPL, and also of the bipolar cell terminals in both the ON and OFF laminae of the IPL (Gong et al, 2006;Stella et al, 2008). The SD rat retinas showed that VGluT1 immunoreactivity followed previously reported patterns (Gong et al, 2006;Stella et al, 2008) (Fig.…”
Section: Kcnq5/vglut1supporting
confidence: 54%
See 1 more Smart Citation
“…Expression of VGLUT2 in retinal ganglion cells has previously been shown in rodents (Fujiyama et al 2003;Johnson et al 2004Johnson et al , 2007Stella et al 2008), and co-localization of VGLUT2 mRNA and melanopsin-ir in the ipRGCs has recently been demonstrated in mice (Johnson et al 2007). In the present study, we used PACAP as a marker for the melanopsin-expressing ipRGCs and their projections, and demonstrated colocalization of PACAP and VGLUT2 in these cells and their nerve terminals in the rat SCN, IGL, and OPN.…”
Section: Discussionmentioning
confidence: 92%
“…To date, three isoforms of VGLUT have been identified, characterized and named VGLUT1, 2, and 3 (reviewed in Takamori 2006). Previous studies in rodents have demonstrated the presence of VGLUT2 mRNA and protein in RGCs (Fujiyama et al 2003;Johnson et al 2004Johnson et al , 2007Stella et al 2008) and colocalization of VGLUT2 and melanopsin in ipRGCs of the mouse retina (Johnson et al 2007). VGLUT2 has been identified in visual target areas of the CNS (Fujiyama et al 2003;Kaneko et al 2002;Kiss et al 2007Kiss et al , 2008Land et al 2004;Sakata-Haga et al 2001;Varoqui et al 2002), but not shown in distinct target areas of the ipRGCs.…”
Section: Introductionmentioning
confidence: 96%